The bases of (im)politeness evaluations: Culture, the moral order and the East–West debate. (16th November 2015) - Spencer-Oatey, Helen; Kádár, Dániel
Abstract : Evaluation is an important aspect of (im)politeness, and this article explores it from an interdisciplinary perspective. It starts by considering the East–West debate in politeness theory and argues that both emic and etic approaches to research can contribute usefully to the deliberations. It then maintains that, if we are to understand the impact of culture on people's (im)politeness evaluations, we need to unpack the concept more thoroughly. It proposes that useful insights can be obtained from Haidt's (e.g. Haidt & Kesebir, 2010) work on moral foundations and Schwartz's (e.g. Schwartz et al., 2012) work on basic values. The article ends by revisiting the East–West debate, discussing the potential impact of other factors such as beliefs and ideologies, and noting the ongoing uncertainties over levels and links between the various concepts explored. It urges pragmaticists and psychologists to engage more fully with each other to help address these challenges.